Pemaknaan Artefak Budaya dan Tuturan Perayaan Keagamaan - Turnomo Rahardjo; Hapsari Dwiningtyas Sulistyani; Lintang Ratri Rahmiaji (Program Studi Ilmu Komunikasi, 2022)
This study was intended to comprehend how faith-based community groups communicated about cultural artifacts such as diverse Christmas celebration speeches. this study employed a phenomenological approach in order to understand the importance of identity expressions from the cultural artifacts associated with the Christmas season. This study found that faith-based community organizations interpret the issues of Christmas speeches or greetings differently. Muhammadiyah